Atividades de retextualização em livros didáticos de português: estudo dos aspectos linguístico-discursivo dos gêneros implicados - Maria Flor de Maio Barbosa Benfica (2013)
This work aims to understand how Portuguese Didatic Books produced in the last decade explore the retextualization as methodological expedient for teaching language, taking into account the linguistic-discursive aspects involved in the gender operation(s) taken as teaching object in the formulation of retextualization activities. We believe that proposing such activities as a strategy for teaching language can create situations for the learner to reflect on the linguistic,textual and discursive regularities of the gender involved, since such activities imply a movement that comprehends the organization of information within the text, the overall scheme of the genre, the textual type, the use of language units and discursive aspects that refer to the event of interaction from which the text emerges, as postulated by Matencio (2002). For this, we analyzed three didatic books collections, further required from Brazilian Culture and Education Ministry, adopted in the editions of 2005, 2008 and 2011 National Didatic Book Plan, for the third and fourth cycles of basic education. After considering documents that parametrize that teaching and academic and scientific production in that area, the analysis shows that the Portuguese Didatic Books collections signal paradigm shifits in teaching language, con The text is seen as teaching unit and the textual/discoursive genres as an object of teaching. The results point that the text production conditions, the definition of the genre to be produced are common points, however, the context of movement of texts is still restricted to the school. It was verified that the activity of retextualization is widely used in the proposed production of oral and written text, but the retextualization process is not taken as the object of teaching and important aspects of the discursive, textual and linguistic diversity (in its strict sense) involved in functioning of the genre are being poorly explored.